Chemie im interstellaren Raum - M. Taube (CHIMIA)
The parameters of the interstellar chemistry have been discussed: the cosmic abundance of elements, the mass and density of the gaseous component in the interstellar space, the temperature, the source of free energy, the stability of the molecules in the flux of ultraviolet light, the role of cosmic rays and the spectral lines of the molecules.